Synthesis, characterization, and performance evaluation of polymeric hindered amine light stabilizers (HALS) in EPDM - Rana, Sravendra; Singh, Raj Pal (E-Polymers, 2007)
Polymeric hindered amine light stabilizer (HALS), wherein the hindered amine functionality was attached to the brominated ethylene-propylene-diene terpolymer (EPDM) was synthesized. The brominated EPDM was synthesized as an intermediate for the synthesis of a new polymeric hindered amine light stabilizer. The grafting and functionalization reactions were characterized by FTIR and (HNMR)-H-1 spectroscopy. The photostabilizing efficiency of this polymeric HALS was studied and compared with conventional HALS under accelerated weathering conditions. The results of the study give evidence for superiority of polymeric HALS over that of melt blended conventional HALS.
Keywords: EPDM; Photostabilization; polymeric HALS